CHAOTIC BEHAVIOR IN THE ROTATIONAL SPEED OF INTERNAL COMBUSTION ENGINES - Volodymyr RUDZINSKYI; Volodymyr LOMAKIN; Serhii MELNYCHUK; Bogdan YEMETS; Oleg LYASHUK; Oleksandr RYABCHUK; Liubomyr SLOBODIAN (Scientific Journal of Silesian University of Technology. Series Transport)
This study investigates the chaotic behavior in the rotational speed of internal combustion engines. High-precision measurements of engine rotational speed were taken at discrete intervals of 0.36 degrees with time measured to a precision of 41 nanoseconds. The data was analyzed using various techniques from chaos theory and nonlinear dynamics, including Lyapunov exponent calculations, phase space reconstruction, and power spectral density analysis. Results reveal that engine rotational speed exhibits complex, chaotic behavior across different operating conditions. Lyapunov exponents ranged from -0.004 to 0.024, indicating varying degrees of chaos from near-stability to strong chaotic behavior. The strongest chaos was observed at certain idle speeds, while full gas conditions showed milder but persistent chaotic characteristics. The study demonstrates that rotational speed fluctuations in internal combustion engines go beyond simple periodic or random variations, suggesting that traditional linear models may be insufficient for accurately predicting and controlling engine behavior. These findings have significant implications for engine design, control strategies, and diagnostics. The authors provide access to the original datasets and analysis code, encouraging further research and collaboration in this field. This work contributes to a deeper understanding of engine dynamics and may lead to the development of more sophisticated, nonlinear approaches to engine analysis and optimization.